Why incorporate plant architecture into trait-based ecology? - Marilyne Laurans; François Munoz; Tristan Charles-Dominique; Patrick Heuret; Claire Fortunel; Sandrine Isnard; Sylvie-Annabel Sabatier; Yves Caraglio; Cyrille Violle (Trends in Ecology & Evolution, 2024)

Contrasting nickel and manganese accumulation and localization in New Caledonian Cunoniaceae - Antony van der Ent; Yohan Pillon; Bruno Fogliani; Vidiro Gei; Tanguy Jaffré; Peter D. Erskine; Guillaume Echevarria; Kathryn M. Spiers; Adrian L. D. Paul; Sandrine Isnard (Plant and Soil, 2022)
Purpose The Cunoniaceae are a major component of the New Caledonian flora with 91 endemic species that are highly unusual in that multiple metals are hyperaccumulated in different species. This makes it an ideal model system for studying the nature of the hyperaccumulation phenomenon. Methods X-ray fluorescence spectroscopy (XRF) scanning of all herbarium collections of the Cunoniaceae was undertaken at the Herbarium of New Caledonia to reveal incidences of nickel (Ni) and manganese (Mn) accumulation. Following on, the Mn hyperaccumulating P. reticulata and the Ni hyperaccumulating P. xaragurensis were selected for detailed follow-up investigations using synchrotron-based X-ray fluorescence microscopy (XFM). Results The systematic XRF screening of herbarium specimens showed that numerous species have high foliar Mn and Ni with species either accumulating Ni or Mn, but not both elements simultaneously. Soil ‘extractable’ Mn and Ni concentrations associated with Pancheria reticulata and P. xaragurensis greatly varies between the species. The XFM data shows that P. reticulata has a distinctive distribution pattern with Mn concentrated in large hypodermal cells. This contrasts with P. xaragurensis where Ni was mainly localized in and around the epidermis, and hypodermal cells were not observed. Conclusions Manganese and Ni accumulation are differently localized in Pancheria species growing on ultramafic soils, which is not explained by contrasting soils conditions, but represents different ecophysiological adaptations.

Soil chemistry, elemental profiles and elemental distribution in nickel hyperaccumulator species from New Caledonia - Vidiro Gei; Guillaume Echevarria; Peter D. Erskine; Sandrine Isnard; Bruno Fogliani; Emmanuelle Montargès-Pelletier; Tanguy Jaffré; Kathryn M. Spiers; Jan Garrevoet; Antony van der Ent (Plant and Soil, 2020)

Twenty years after Jaffré et al. (1998), is the system of protected areas now adequate in New Caledonia? - Thomas Ibanez; Philippe Birnbaum; Gildas Gâteblé; Vanessa Hequet; Sandrine Isnard; Jérôme Munzinger; Yohan Pillon; Robin Pouteau; Hervé Vandrot; Tanguy Jaffré (Biodiversity and Conservation, 2019)

How did the ultramafic soils shape the flora of the New Caledonian hotspot? - Sandrine Isnard; Laurent L’huillier; Frédéric Rigault; Tanguy Jaffré (Plant and Soil, 2016)

New Caledonia: a Pleistocene refugium for rain forest lineages of relict angiosperms - Robin Pouteau; Santiago Trueba; Taylor S. Feild; Sandrine Isnard (Journal of Biogeography, 2015)
Aim In New Caledonia, relictual angiosperm lineages are over‐represented. However, the mechanisms responsible for such a distribution remain unclear. Two key hypotheses are that: (1) the diversity reflects adaptation to ultramafic substrates that ecologically filtered plant colonists; and (2) the diversity stems from wet climatic conditions that have persisted in New Caledonia during the late Quaternary while Australia and some nearby islands experienced widespread extinction events. Here, we investigate which hypothesis better explains the disharmony of relict angiosperms in New Caledonia. Location New Caledonia (South West Pacific Ocean). Methods We built species distribution models from herbarium data to determine the environmental correlates for 60 relict angiosperm taxa. Environmental variables used to characterize habitats included vegetation, substrate, and climate variables. We then tested whether the variety of xylem conduit structures borne by New Caledonian relict angiosperms, which is expected to affect plant hydraulic capacity, was correlated with habitat preference. Finally, we analysed species prevalence on different substrates and projected habitat size and distribution to the Last Glacial Maximum ( LGM ). Results We found a clear habitat preference among relict angiosperms for rain forests located on non‐ultramafic substrates, with the exception of taxa bearing true vessels with simple perforation plates, which harboured a wider habitat breadth. We also showed that these rain forest habitats experienced a range reduction and an eastward shift during the LGM , forming two refugial areas located on the warm and rainy east coast of Grande Terre. Main conclusions Prevalence of relict angiosperms in habitats characterized by low evaporative demand appears to be related to xylem hydraulic limitations. The disharmony of relict angiosperms in New Caledonia therefore arose from the persistence of rain forests in the island despite global fluctuations in climate during the Quaternary that affected floras in the region. Our study offers a new model to explain why certain angiosperm families are disharmonically represented in New Caledonia.

Universal hydraulics of the flowering plants: vessel diameter scales with stem length across angiosperm lineages, habits and climates - Mark E. Olson; Tommaso Anfodillo; Julieta A. Rosell; Giai Petit; Alan Crivellaro; Sandrine Isnard; Calixto León‐Gómez; Leonardo O. Alvarado‐Cárdenas; Matiss Castorena (Ecology Letters, 2014)
Angiosperm hydraulic performance is crucially affected by the diameters of vessels, the water conducting conduits in the wood. Hydraulic optimality models suggest that vessels should widen predictably from stem tip to base, buffering hydrodynamic resistance accruing as stems, and therefore conductive path, increase in length. Data from 257 species (609 samples) show that vessels widen as predicted with distance from the stem apex across angiosperm orders, habits and habitats. Standardising for stem length, vessels are only slightly wider in warm/moist climates and in lianas, showing that, rather than climate or habit, plant size is by far the main driver of global variation in mean vessel diameter. Terminal twig vessels become wider as plant height increases, while vessel density decreases slightly less than expected tip to base. These patterns lead to testable predictions regarding evolutionary strategies allowing plants to minimise carbon costs per unit leaf area even as height increases.

Present trans‐Pacific disjunct distribution of A ristolochia subgenus I sotrema ( A ristolochiaceae) was shaped by dispersal, vicariance and extinction - Favio González; Sarah T. Wagner; Karsten Salomo; Lars Symmank; Marie‐Stéphanie Samain; Sandrine Isnard; Nick P. Rowe; Christoph Neinhuis; Stefan Wanke (Journal of Biogeography, 2014)
Aim I sotrema is a monophyletic subgenus of A ristolochia with species in E ast A sia and N orth/ C entral A merica. Earlier studies, based on limited sampling, suggested that the A sian and A merican species do not form two reciprocal sister clades. We reconstructed phylogenetic relationships within I sotrema to infer the biogeographical events that have shaped its present‐day distribution. Location E astern A sia, N orth A merica, M exico, C entral A merica. Methods We performed parsimony and Bayesian phylogenetic analyses of 54 accessions using three chloroplast regions. The temporal origins were traced with relaxed phylogenetics and penalized likelihood using fossil calibrations; these methods were combined with ancestral area reconstructions in a comparative approach using statistical dispersal–vicariance analysis ( S‐DIVA ) and dispersal–extinction–cladogenesis ( DEC ) analyses. Results The ancestors of the herbaceous eastern N orth A merican species and the woody species probably diverged during the O ligocene. The woody species form a Neotropical and a N orth A merican/ E astern A sian clade. Diversification in the Neotropical and N orth A merican/ E astern A sian clades occurred mostly in the M iocene. In the latter clade, two further intercontinental splits are reconstructed: between the exclusively western N orth A merican A ristolochia californica and most of the A sian taxa, and between A . manshuriensis and A . tomentosa . Main conclusions The present distribution of I sotrema developed via a number of dispersal, vicariance and extinction events. The disjunct distributions observed may be the result mainly of non‐synchronous events (e.g. a decrease of mean annual temperature in the O ligocene and the development of unfavourable conditions across the B ering land bridge) that were responsible for the fragmentation of the mesophytic forests. Later diversifications may be correlated with events such as the orogeny of the W estern C ordillera and A ppalachian M ountains, the development of extensive grasslands in N orth A merica, and the mainland extension of C entral A merica southwards to western and central P anama.

Diversity of Mechanical Architectures in Climbing Plants: An Evolutionary Perspective - Nick Rowe; Sandrine Isnard; Thomas Speck (Journal of Plant Growth Regulation, 2004)